Implementação inicial da RFC 6897 - Silva, Alan Castro (Universidade Federal de São Carlos, 2016)
The Multipath TCP (MPTCP) protocol allows applications to better explore the network resources available to multi-connected devices such as mobile phones or multi-homed systems. Here, some advantages are envisioned: bandwidth aggregation, the ability to maintain the connection, if one of the network path fails and the use of multiple paths. To extend these capabilities to the application, RFC 6897 defines an API to better control each of MPTCP’s subflows, so that these can be added or removed as needed. This work presents an initial API implementation as defined in RFC 6897. We implemented some functions described in the document, such as protocol on/o, check existent subflows and add new subflows. To test the API and validate our implementation we built an HTTP application that detects elephant flows and uses the API for open new subflows using the original TCP connection. Some tests were performed in a network using a cubic topology and showed that the API utilization decreased the Flow Completion time of TCP connections.
Initial implementation of RFC 6897
Keywords: Rede de computador - protocolos; Computer network protocols; MPTCP; Network Transport Protocols; Protocolos de Transporte de Rede; Interface de Programação para Aplicações em Redes; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO